The role of fiscal policy measures in mitigating the effects of the Covid-19 crisis in Germany - Michael Christl; Silvia De Poli; Tine Hufkens; Andreas Peichl; Mattia Ricci (EconPol Forum, 2023)
We use a novel methodology for modeling the socio-economic impacts of economic crisis in Germany, and apply it to estimate the impact of the Covid-19 pandemic. We estimate that German households lost more than 3 percent of their market income in 2020 due to the Covid-19 pandemic, with the effect being strongly regressive. However, the fall in market income was largely offset by the tax-benefit system, which softened the reduction in disposable income to a more modest 0.5 percent. Our study highlights the importance of shorttime work and discretionary policy measures (the Covid-19 one-off child benefit and the increase in the tax allowance for single parents) in cushioning the impact of the Covid-19 crisis. The strong income-stabilizing property of shorttime work and discretionary policy measures for low-income earners has also helped overcome a strong reduction in household demand
Keywords: 330